Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1166/jnn.2011.3826
|View full text |Cite
|
Sign up to set email alerts
|

Template Assisted Electrochemical Growth of Cobalt Nanowires: Influence of Deposition Conditions on Structural, Optical and Magnetic Properties

Abstract: The influence of electrodeposition potential, pH, composition and temperature of the electrolytic bath on the structure of cobalt nanowires arrays electrodeposited into anodic aluminum oxide (AAO) porous membranes is reported. XRD, SEM, and TEM analysis were employed to characterize structural (crystal phase, crystallographic texture, and grain size), and morphological nanowire properties. It was confirmed that at pH 2 the electrodeposition potential has not influence on the preferred crystallographic orientat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
1
15
1
Order By: Relevance
“…6,7 This is typically qualitatively concluded from the differences in the hysteresis loops shape between parallel and perpendicular applied magnetic field configurations.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…6,7 This is typically qualitatively concluded from the differences in the hysteresis loops shape between parallel and perpendicular applied magnetic field configurations.…”
mentioning
confidence: 96%
“…[3][4][5][6][7] Particularly, it has been shown that pH-controlled electroplating enables the switching between fcc and hcp-Co phases, which modifies the magnetization easy axis from parallel to perpendicular to the wires. 6,7 This is typically qualitatively concluded from the differences in the hysteresis loops shape between parallel and perpendicular applied magnetic field configurations.…”
mentioning
confidence: 99%
“…A special attention in recent investigations is focused on one-dimensional magnetic nanostructures such as nanowires. The control of geometrical parameters of nanowires and their structure determined by process parameters, allows one to tune the magnetic properties [1,2], offering a variety of applications from high density magnetic recording media to high quality sensors and microwave devices [3]. The magnetic multilayered nanowires composed of alternatively aligned magnetic and non-magnetic layers represent an important family of materials attractive for GMR sensor applications [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In Co nanowires, the crystalline structure can be tuned by varying the growth parameters such as applied voltage, dimensions (diameter, length) or annealing and deposition under external magnetic fields [13][14][15]. Particularly, the pH-controlled electroplating enables the switching between fcc and hcp-Co crystal phases, which modifies the magnetization easy axis from parallel to perpendicular to the wires [16].…”
Section: Introductionmentioning
confidence: 99%